2005
DOI: 10.1042/cs20050135
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of systemic oxygen flux by acute exercise and normobaric hypoxia: implications for reactive oxygen species generation

Abstract: Maximal exercise in normoxia results in oxidative stress due to an increase in free radical production. However, the effect of a single bout of moderate aerobic exercise performed in either relative or absolute normobaric hypoxia on free radical production and lipid peroxidation remains unknown. To examine this, we randomly matched {according to their normobaric normoxic VO2peak [peak VO2 (oxygen uptake)]} and assigned 30 male subjects to a normoxia (n = 10), a hypoxia relative (n = 10) or a hypoxia absolute (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…The significant positive correlation between DNA damage and PBN-adduct provides a tentative association and link between the two molecules. Alkoxyl radicals are derived from oxidative damage to lipid cellular membranes via metal-catalyzed reactions [Davison et al, 2006]. All hyperfine coupling constants measured in the present investigation are synonymous with the detection of alkoxyl radicals (a N 5 13.7 G and ab H 5 1.8 G) and are consistent with published data [Davison et al, 2006[Davison et al, , 2008.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The significant positive correlation between DNA damage and PBN-adduct provides a tentative association and link between the two molecules. Alkoxyl radicals are derived from oxidative damage to lipid cellular membranes via metal-catalyzed reactions [Davison et al, 2006]. All hyperfine coupling constants measured in the present investigation are synonymous with the detection of alkoxyl radicals (a N 5 13.7 G and ab H 5 1.8 G) and are consistent with published data [Davison et al, 2006[Davison et al, , 2008.…”
Section: Discussionsupporting
confidence: 86%
“…Alkoxyl radicals are derived from oxidative damage to lipid cellular membranes via metal-catalyzed reactions [Davison et al, 2006]. All hyperfine coupling constants measured in the present investigation are synonymous with the detection of alkoxyl radicals (a N 5 13.7 G and ab H 5 1.8 G) and are consistent with published data [Davison et al, 2006[Davison et al, , 2008. The systemic increase in the alkoxyl free radical concentration and LOOH following incremental exercise along with the positive correlation may suggest free radical-mediated damage to DNA following a short bout of moderate-and high-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The method of Altman [16] was used to determine the number of subjects (n ¼ 28, excluding a 20% drop out rate) required for this study (using previously published lipid data, [17]). Data were analysed using parametric statistics following confirmation of a normal distribution by Shapiro Wilks tests.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential study designs are also used to a great extent in investigations of hypoxia by exposure in chambers or masks (42)(43)(44)(45)(46), but there are also well-controlled studies (47)(48)(49)(50)(51). Four of the well-controlled studies reported a relationship between exposure to hypoxia and oxidative damage to both DNA and lipids (47,48,50,51), whereas one investigation found no effect of hypoxia (49). Data based on sequential studies indicate hypoxia-induced effects on at least one biomarker of lipid or DNA oxidation (12-16, 20, 23, 24, 34-42, 45, 46), except two studies that happens to be short-term (less than 10 min) exposure to hypoxia (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, oxygen level decreased over time in studies of the ascend to the summit of San Pedro y San Pablo volcano (46) and the simulated ascend to Mt Everest (37), but it is impossible to split the time component from the effect of hypoxia. Figure 1 outlines the results of an overall analysis where studies have been stratified into those with exposures lasting 1 h or less (43)(44)(45)48), between 1 and 24 h (16,42,46,47,50,51), and between 24 h and 8 weeks (12-16, 20, 23, 34-41). This analysis indicates that the effect observed after days or weeks of hypoxia is larger than at earlier time point, but it should also be recognized that most of these studies are poorly controlled and it may just be an effect of confounding factors.…”
Section: Dose-response Relationshipmentioning
confidence: 99%